2020
DOI: 10.1111/jth.14661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood flow on platelets, leukocytes, and extracellular vesicles in thrombosis of simulated neonatal extracorporeal circulation

Abstract: Background: Extracorporeal membrane oxygenation (ECMO) has frequent and sometimes lethal thrombotic complications. The role that activated platelets, leukocytes, and small (0.3-micron to 1-micron) extracellular vesicles (EVs) play in ECMO thrombosis is not well understood.Objectives: To test the effect of blood flow rate on the generation of activated platelets, leukocytes, and EVs in a simulated neonatal ECMO circuit using heparinized human whole blood. Methods: Simulated neonatal roller pump circuits circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 56 publications
(63 reference statements)
2
39
0
1
Order By: Relevance
“…In response to the continuous exposure to non-physiological conditions (e.g. flow rates and associated shear stress) and significant release of inflammatory mediators during ECMO ( 16 , 18 , 34 , 35 , 37 , 39 , 65 67 ), cells of the endothelial lining are likely to convert into an activated state ( 68 , 69 ). This can subsequently elevate leukocyte adhesion [from phenotypic modulation ( 13 , 17 , 18 , 34 36 )] onto either the artificial surface of the ECMO circuit ( 23 , 24 , 70 ) or the endothelium itself ( 68 , 69 ), possibly acting as a consistent regulator of cell attachment in vivo .…”
Section: Ecmo As a Second “Hit” To Leukocyte Pathophysiology In Critimentioning
confidence: 99%
See 2 more Smart Citations
“…In response to the continuous exposure to non-physiological conditions (e.g. flow rates and associated shear stress) and significant release of inflammatory mediators during ECMO ( 16 , 18 , 34 , 35 , 37 , 39 , 65 67 ), cells of the endothelial lining are likely to convert into an activated state ( 68 , 69 ). This can subsequently elevate leukocyte adhesion [from phenotypic modulation ( 13 , 17 , 18 , 34 36 )] onto either the artificial surface of the ECMO circuit ( 23 , 24 , 70 ) or the endothelium itself ( 68 , 69 ), possibly acting as a consistent regulator of cell attachment in vivo .…”
Section: Ecmo As a Second “Hit” To Leukocyte Pathophysiology In Critimentioning
confidence: 99%
“…Two recently published ex vivo studies reported ECMO flow rates and the mediated non-physiological shear stress as potential influencing factors ( 37 , 39 ). During continuous ECMO blood flow, wall shear stress within the rigid ECMO circuit increases to non-physiological levels as blood flow elevates.…”
Section: What Are the Causes Of Ecmo-related Leukocyte Modulation?mentioning
confidence: 99%
See 1 more Smart Citation
“…[162][163][164][165] However, a similar role of exosomes and MVs is assumed in COVID-19 as other virus infectious diseases. [166][167][168][169][170] In particular, concerning thrombosis, there is no doubt that COVID-19 causes more symptoms in comparison with the past virus infectious disease. 171 Accumulation of important reports of EVs in conjunction with COVID-19 is expected in the future.…”
Section: Evs and Coagulatory Abnormalities During Viral Infectionmentioning
confidence: 99%
“…With great interest, we read the work of Meyer et al, who used a mock neonatal extracorporeal membrane oxygenation (ECMO) circuit to investigate the impact of varying flow rates on platelet activation, leukocytes, extracellular vesicles, and thrombin generation in vitro 1 . We appreciate the authors’ efforts toward refining treatment to prevent device‐related thrombosis as a major cause of morbidity and mortality in this particular group of patients.…”
mentioning
confidence: 99%